Microbial contamination of procedure gloves after opening the container and during exposure in the environment - Ferreira, Adriano Menis; Andrade, Denise de; Haas, Vanderlei José (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to quantify the colony forming units (cfu) on latex procedure gloves in the beginning, middle, and end of the containers in real (professional) and controlled (researcher) gloving situations; evaluate the microbial load of the gloves, considering the time of exposure in the environment. This comparative prospective study was conducted at an intensive care unit of a teaching hospital. The microbiological data was collected from the gloves using digital-pressure. Microbiological evaluations were performed on 186 pairs of gloves: 93 in the control group and 93 in real gloving situations. In the control group, the average cfu was 4.7 against 6.2 in the real gloving situation. Hence, no statistically significant difference was found (p=.601). In addition, the cfu values of gloves in the beginning, middle and end of the containers also did not show any significant differences (p>;.05). The most common strain was Staphylococcus spp. The time of exposure in the environment did not increase the cfu value of the latex gloves.